The Relationship of Self Regulated Learning to Student Engagement in High School Students - Indah Kartika Asih, Febiyanti Fitri; Hardew, Ayatullah Kutub (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
In Indonesia, there are still many students who have no attachment to school and are not active in the learning process, which means that the level of student engagement is still low. This condition shows that schools have not succeeded in optimizing educational goals, so students feel bored, their interest in learning decreases, and often do not participate in learning at school, some even leave school. The purpose of this study was to determine the relationship of self-regulated learning to student engagement in students of State Senior High School 1 Surakarta. The research method is quantitative with stratified random sampling technique. The measurement tools used in this study were the self-regulated learning scale and the student engagement scale, and the data were analyzed using simple regression. The results showed that the correlation coefficient value was r = 0.863, p = < 0.01 (p < 0.05). This indicates that there is a positive relationship between self-regulated learning and student engagement at State Senior High School 1 Surakarta.